2004
DOI: 10.1532/ijh97.03127
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrias in Japan: Compilation of All Cases Reported through 2002

Abstract: The first case of porphyria on record in Japan was a patient with congenital erythropoietic porphyria (CEP) reported by Sato and Takahashi in 1920. Since then until the end of December 2002, 827 cases of porphyrias have been diagnosed from characteristic clinical and/or laboratory findings (463 males, 358 females, and 6 of unknown sex). Essentially all inherited porphyrias have been found in Japan, with the incidences and clinical symptoms generally being similar to those reported for other countries. The male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
3
13
0
1
Order By: Relevance
“…These differences can be related to the prevalence and penetrance of EPP in these populations. EPP has never been demonstrated in black sub-Saharan Africans, and 51% of Japanese EPP cases occurred in families with some other history of EPP compared with only 15% of French case [8,18]. Indeed, we performed a literature search of all the EPP patients reported in the Chinese medial literature using the CBM database (Chinese Biological Medicine on disc) and only found about 100 EPP patients that were reported.…”
Section: Discussionmentioning
confidence: 99%
“…These differences can be related to the prevalence and penetrance of EPP in these populations. EPP has never been demonstrated in black sub-Saharan Africans, and 51% of Japanese EPP cases occurred in families with some other history of EPP compared with only 15% of French case [8,18]. Indeed, we performed a literature search of all the EPP patients reported in the Chinese medial literature using the CBM database (Chinese Biological Medicine on disc) and only found about 100 EPP patients that were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of IVS3-48C will have an effect on the penetrance of EPP phenotype among affected families as well as on the prevalence of the disease in a particular population. Indeed, in an extensive epidemiological study on porphyrias in the Japanese population, Kondo et al 8 showed that 51% of the EPP cases occurred in families in which other members had previous history of EPP. However, the same situation occurs only in 15% of the French cases, suggesting that the penetrance of EPP is higher in the Japanese population than in the French population.…”
Section: Autosomal Dominant Traitmentioning
confidence: 99%
“…62 We therefore compared the data from the study by Kondo et al 8 with that of a Swiss study we conducted a few years ago in order to assess the situation in these two populations. 34 In the study by Kondo et al, 8 a total of 154 EPP cases were recorded during the time period from 1920 and 2002. And in our study, a total 45 EPP cases were registered from 1993 to 2007.…”
Section: Autosomal Dominant Traitmentioning
confidence: 99%
“…12,150,151 The prevalence of gall stone disease in EPP varies in different publications, from 4% to 20%. 12,[152][153][154] Less than five 155 , up to 25% 156,157 develop advanced liver disease. The high frequencies in the latter studies probably reflect the referral pattern in one study 156 and in the other the liver disease was not well defined.…”
Section: A History Of Liver Transplantationmentioning
confidence: 99%
“…The high frequencies in the latter studies probably reflect the referral pattern in one study 156 and in the other the liver disease was not well defined. 157 The most serious liver complication in EPP is cholestatic liver failure. In some patients, the course of the liver disease is insidious, and cirrhosis is eventually detected.…”
Section: A History Of Liver Transplantationmentioning
confidence: 99%